The Effects of Alternative Sharing Arrangements on Employment: Preliminary Evidence From Britain - Derek C. Jones; Jeffrey Pliskin (Levy Economics Institute of Bard College, 1988)
A sample of British firms with diverse sharing arrangements is used to investigate the effects of profit sharing on employment levels. Employment effects are sometimes significant but depend upon the measure of profit sharing, how the dynamics are modeled, and whether measures of employee participation in decision making are included in the estimating equation. Using a continuous measure of profit sharing, employment effects, which typically range from -6% to 6% are much more modest than those obtained by some other researchers. Most findings are not dramatically affected by estimating for separate time periods, individual industries or separately for larger firms.
Keywords: 330